Trio Dispa: Effort to Establish Family Health Experts in Acute Respiratory Infections - Kalsum, Wa Ode Umi; Sabriyati, Wa Ode Nur Isnah; Utami, Nurfadilah; Monalisa, Monalisa (Indonesian Contemporary Nursing Journal (ICON Journal), 2020)
Introduction: Acute Respiratory Infections (ARI) is classified into non-Pneumonia (upper respiratory infection) and Pneumonia (lung or alveoli tissue) ARI. ARI is the second leading cause of death that occurs in infants in Indonesia. Trigger factors that can cause ARI include poor lighting system, unhealthy environment, incomplete infant immunization status, low infant nutritional status, low economic and maternal education status, as well as less optimal health care workers in preventing and controlling the incidence of acute respiratory distress syndrome. The study aims to determine the effectiveness of TRIO DISPA (Three colours detection and early intervention for acute respiratory infections by tabletop learning method) to increase the mother’s knowledge in identifying, interpreting and early treating of ARI symptoms disease in the working area of Pampang Public Health Centre, Makassar City. Method: This study is Quasy Experimental Design which used the Pretest-Postest without Control Group Design. The sample of this study is 20 respondents and use Wilcoxon Sign Rank Test to analyse the data. Results: The study revealed that the family caregiver shows a difference between before and after implementing the TRIO DISPA program which able to interpreted tabletop case simulation. The increase of knowledge based on the pre-post test result using the Wilcoxon test (p=0,001). Conclusion: The TRIO DISPA program can make it easier for the public to understand ARI disease and handling its signs and symptoms.